If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7p + 16 = 2p + 4 + 3p Reorder the terms: 16 + -7p = 2p + 4 + 3p Reorder the terms: 16 + -7p = 4 + 2p + 3p Combine like terms: 2p + 3p = 5p 16 + -7p = 4 + 5p Solving 16 + -7p = 4 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. 16 + -7p + -5p = 4 + 5p + -5p Combine like terms: -7p + -5p = -12p 16 + -12p = 4 + 5p + -5p Combine like terms: 5p + -5p = 0 16 + -12p = 4 + 0 16 + -12p = 4 Add '-16' to each side of the equation. 16 + -16 + -12p = 4 + -16 Combine like terms: 16 + -16 = 0 0 + -12p = 4 + -16 -12p = 4 + -16 Combine like terms: 4 + -16 = -12 -12p = -12 Divide each side by '-12'. p = 1 Simplifying p = 1
| 7+4x=-2x+11 | | -96-2x=24-12x | | 0.5x+0.6(2x+1)=5.7 | | 25-x=y | | 5x-4y-10z=-100 | | -x-133=9x+47 | | 2x-10=x-11 | | 132x^2-23x-132=0 | | 3x+12-2=-8 | | -3x-17=-6x+34 | | 7y=31-3x | | 5x+5=7x+12 | | 44+x-3+2x+1=180 | | 4(-m-7n)= | | 9x-55=110+2x | | -1+3x=9+-2x | | 6x+2=5(x-5)+7 | | 1/5(x-2)-(2x-3)=2/3(4x+1)-1/6(2x+7) | | 6x-26=12+4x | | 1-7y=3-8y | | 72+80+106+4x=360 | | 4x+8=-3x-20 | | -102-10x=-2x+138 | | 6p+9=5p+17 | | Y=2(0)-9 | | -7x-11=9x+25 | | 3(2r-2)=30 | | 3x-63=45+12x | | 28=4y^2 | | 4x=x+95 | | 5-4y=2-5y | | 5y-1+2y=3 |